Fluorination of 6-methyluracil and its nlcleosides. - Cech, D (1977)
6-Methyluracil and its perbenzoylated 1-(beta-D-ribofuranosyl) and 1-(2-deoxy-beta-D-ribofuranosyl) derivatives afford on treatment with elemental fluorine in acetic acid solutions, the corresponding derivatives of 5-fluoro-6-methyluracil and 5-fluoro-6-fluoromethyluracil. The free nucleosides have been obtained from the protected derivatives by methanolysis. The CH2F linkage in 5-fluoro-6-fluoromethyluracil derivatives is stable towards hydrolysis and nucleophilic agents.